Regional age structure, human capital and innovation: Is demographic ageing increasing regional disparities? - Terry Gregory; Roberto Patuelli (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Demographic change is expected to affect labour markets in very different ways on a regional scale. The objective of this paper is to explore the spatio-temporal patterns of recent distributional changes in the workers age structure, innovation output and skill composition for German regions by conducting an Exploratory Space-Time Data Analysis (ESTDA). Beside commonly used tools, we apply newly developed approaches which allow investigating the space-time dynamics of the spatial distributions. We include an analysis of the joint distributional dynamics of the patenting variable with the remaining interest variables. Overall, we find strong clustering tendencies for the demographic variables and innovation that constitute a great divide across German regions. The detected clusters partly evolve over time and suggest a demographic polarization trend among regions that may further reinforce the observed innovation divide in the future.
Keywords: J11; O31; R11; R12; R23; 330; innovation; workforce age structure; exploratory space-time data analysis; regional disparities